2013
DOI: 10.1038/nsmb.2698
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of UG-rich RNA recognition by the human splicing factor TDP-43

Abstract: TDP-43 encodes an alternative-splicing regulator with tandem RNA-recognition motifs (RRMs). The protein regulates cystic fibrosis transmembrane regulator (CFTR) exon 9 splicing through binding to long UG-rich RNA sequences and is found in cytoplasmic inclusions of several neurodegenerative diseases. We solved the solution structure of the TDP-43 RRMs in complex with UG-rich RNA. Ten nucleotides are bound by both RRMs, and six are recognized sequence specifically. Among these, a central G interacts with both RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
505
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(532 citation statements)
references
References 49 publications
27
505
0
Order By: Relevance
“…These results suggest that RRM1 and RRM2 interact in the absence of RNA, with interdomain interactions stabilizing the native state of each RRM domain by 0.9 kcal mol Ϫ1 (Table 1). Indeed, a recent NMR study on the tethered RRM domain revealed that in the absence of RNA, the two RRMs do not tumble independently of one another (43), further supporting mutual stabilizing interactions between the domains. The Trp FL also suggests that RRM1 is completely unfolded at the first intermediate, I1, of the CD equilibrium unfolding profile.…”
Section: Table 1 Thermodynamic Parameters Of the Isolated And Tetherementioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that RRM1 and RRM2 interact in the absence of RNA, with interdomain interactions stabilizing the native state of each RRM domain by 0.9 kcal mol Ϫ1 (Table 1). Indeed, a recent NMR study on the tethered RRM domain revealed that in the absence of RNA, the two RRMs do not tumble independently of one another (43), further supporting mutual stabilizing interactions between the domains. The Trp FL also suggests that RRM1 is completely unfolded at the first intermediate, I1, of the CD equilibrium unfolding profile.…”
Section: Table 1 Thermodynamic Parameters Of the Isolated And Tetherementioning
confidence: 99%
“…Note that the solution structure of RRMc is unknown and predicted to be much different from that mapped on RRM2 (Protein Data Bank entry 1wf0) due to removal of secondary structural elements in the protein core. E, NMR structure of the tethered RRMs with RNA (Protein Data Bank entry 4bs2) with RNA shown in gray (43). The secondary structure elements are colored as shown in C and D. The RNA-binding residues and intrinsic fluorophores are shown as sticks.…”
Section: Rrm Domains Are Monomeric and Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). The NLS and NES regulate the shuttling of TDP-43 between the nucleus and the cytoplasm (5), whereas the RRM1 and RRM2 are responsible for binding to nucleic acids including single-or double-stranded DNA/RNA (5)(6)(7)(8). The prion-like domain mediates protein-protein interactions between TDP-43 and other hnRNP members (9), which also hosts most known ALS-associated TDP-43 mutations.…”
mentioning
confidence: 99%
“…Limited similarity to the preceding guanine lies only in a common syn-conformation with 3 0 endo sugar pucker. Finally, in the complex of tandem RRM domains of TDP-43 in complex with GUGUGAAUGAAU (PDB 4BS2) 18 , the nucleotide conformation of the bound G3-U4-G5 is again similar to that of G4, G5 and G6 in complex with SUP-12, but with dissimilar types of protein contact. Interestingly, a guanine is recognized by both RRM domains reminiscent of the interface between ASD-1 and SUP-12 in the ternary complex.…”
Section: Discussionmentioning
confidence: 99%